A Semantic Model for Enhancing Network Services Management and Auditing - Rodrigues, Carlos (2011)
The road toward ubiquity, heterogeneity and virtualization of network services and resources urges for a formal and systematic approach to network management tasks. In particular, the semantic characterization and modeling of services provided to users assume an essential role in fostering autonomic service management, service negotiation and auditing. This paper is centered on the definition of an ontology for multiservice IP networks which intends to address multiple service management goals, namely: (i) to foster client and service provider interoperability; (ii) to manage network service contracts, facilitating the dynamic negotiation between clients and ISPs; (iii) to access and query SLA/SLSs data on an individual or aggregated basis to assist service provisioning in the network; and (iv) to sustain service monitoring and auditing. In order to take full advantage of the proposed semantic model, a service model API is provided to allow service management platforms to access the ontological contents. This ontological development also takes advantage of SWRL to discover new knowledge, enriching the possibilities of systems described using this support.